Challenges of sustainable behavior and possible solutions to overcome barriers through marketing and communication. - (:unkn) unknown (My University, 2020)
Ο σύγχρονος τρόπος ζωής και τα περιβαλλοντικά ζητήματα που απορρέουν από τις ανθρώπινες δραστηριότητες και συνήθειες στον 21ο αιώνα καθιστούν αναγκαία την εύρεση νέων τρόπων επιχειρηματικότητας και προώθησης προϊόντων. Η εν λόγω πτυχιακή εργασία, έπειτα από ανάλυση των δύο άρθρων των Vinod Kumara, Zillur Rahmanb, A. A. Kazmic and Praveen Goyald με τίτλο Evolution of sustainability as marketing strategy: Beginning of new era και των Katherine White, Rishad Habib, and David J. Hardisty με τίτλο How to SHIFT Consumer Behaviors to be More Sustainable: A Literature Review and Guiding Framework, στοχεύει στην ανάλυση των τρόπων με τους οποίους οι υπεύθυνοι μάρκετινγκ ανά τον κόσμο μπορούν να κάνουν πιο ανταγωνιστικά τα προϊόντα τους σε μια εποχή που αλλάζει συνεχώς σεβόμενοι το περιβάλλον, αλλά και πώς ο ίδιος ο καταναλωτής μπορεί να αποκτήσει οικολογικές συνήθειες μέσα από τις αγοραστικές του επιλογές. Στην εργασία, γίνεται ειδική αναφορά και σε ένα καινοτόμο ψυχολογικό πλαίσιο που παρουσιάζεται με το ακρώνυμο SHIFT και που σκοπό έχει την καλύτερη κατανόηση και αντιμετώπιση των προκλήσεων που παρουσιάζονται στην προσπάθεια συνεργασίας του τομέα του μάρκετινγκ με τον τομέα της βιωσιμότητας και της προστασίας του περιβάλλοντος.

The modern way of life and the environmental issues arising from human activities and habits in the 21st century, highlight the need for new ways of doing business and promoting products. This thesis, after the analysis of two articles by Vinod Kumara, Zillur Rahmanb, AA Kazmic and Praveen Goyald entitled Evolution of sustainability as marketing strategy: Beginning of new era and Katherine White, Rishad Habib, and David J. Hardisty entitled How to SHIFT Consumer Behaviors to be More Sustainable: A Literature Review and Guiding Framework, aims to analyze the ways in which marketing managers around the world can make their products more competitive at a constantly changing era with respect to the environment, but also how the consumers themselves can acquire ecological habits through their buying choices. In this paper, special reference is made to an innovative psychological framework presented under the acronym SHIFT, which aims to better understand and address the challenges that arise during the matching of the field of marketing with the field of sustainability and environmental protection.
Keywords: βιωσιμότητα, μάρκετινγκ, καταναλωτική συμπεριφορά, περιβαλλοντική συμπεριφορά; Sustainability, SHIFT, consumer behavior, ecological behavior, green marketing